FVIII-specific human chimeric antigen receptor T-regulatory cells suppress T- and B-cell responses to FVIII - Yoon, Jeongheon; Schmidt, Anja; Zhang, Ai-Hong; Königs, Christoph; Kim, Yong Chan; Scott, David W. (Blood, 2017)
Replacement therapy with factor VIII (FVIII) is used in patients with hemophilia A for treatment of bleeding episodes or for prophylaxis. A common and serious problem with this therapy is the patient's immune response to FVIII, because of a lack of tolerance, leading to the formation of inhibitory antibodies. Development of tolerogenic therapies, other than standard immune tolerance induction (ITI), is an unmet goal. We previously generated engineered antigen-specific regulatory T cells (Tregs), created by transduction of a recombinant T-cell receptor (TCR) isolated from a hemophilia A subject's T-cell clone. The resulting engineered T cells suppressed both T- and B-cell effector responses to FVIII. In this study, we have engineered an FVIII-specific chimeric antigen receptor (ANS8 CAR) using a FVIII-specific scFv derived from a synthetic phage display library. Transduced ANS8 CAR T cells specific for the A2 domain proliferated in response to FVIII and ANS8 CAR Tregs were able to suppress the proliferation of FVIII-specific T-effector cells with specificity for a different FVIII domain in vitro. These data suggest that engineered cells are able to promote bystander suppression. Importantly, ANS8 CAR-transduced Tregs also were able to suppress the recall antibody response of murine splenocytes from FVIII knockout mice to FVIII in vitro and in vivo. In conclusion, CAR-transduced Tregs are a promising approach for future tolerogenic treatment of hemophilia A patients with inhibitors. •Generation and functional analysis of FVIII-specific human CAR Tregs.•Specific regulation of FVIII responses by engineered human CAR Tregs.